Existence of entropy solutions for some nonlinear problems in Orlicz spaces. (14th March 2002) - Benkirane, A.; Bennouna, J.
Abstract : We study in the framework of Orlicz Sobolev spacesW 0 1 L M ( Ω ), the existence of entropic solutions to the nonlinear elliptic problems:− div a ( x, u, ∇ u ) + div Φ ( u ) = f in Ω, for the case where the second member of the equationf ∈ L 1 ( Ω ), andΦ ∈ ( C 0 ( ℝ ) ) N .